Co-electrolysis of seawater and carbon dioxide inside a microfluidic reactor to synthesize speciality organics - Rarotra, Saptak (2023)
We report co-electrolysis of seawater and carbon dioxide (CO2) gas in a solar cell-integrated membraneless microfluidic reactor for continuous synthesis of organic products. The microfluidic reactor was fabricated using polydimethylsiloxane substrate comprising of a central microchannel with a pair of inlets for injection of CO2 gas and seawater and an outlet for removal of organic products. A pair of copper electrodes were inserted into microchannel to ensure its direct interaction with incoming CO2 gas and seawater as they pass into the microchannel. The coupling of solar cell panels with electrodes generated a high-intensity electrical field across the electrodes at low voltage, which facilitated the co-electrolysis of CO2 and seawater. The paired electrolysis of CO2 gas and seawater produced a range of industrially important organics under influence of solar cell-mediated external electric field. The, as synthesized, organic compounds were collected downstream and identified using characterization techniques. Furthermore, the probable underlying electrochemical reaction mechanisms near the electrodes were proposed for synthesis of organic products. The inclusion of greenhouse CO2 gas as reactant, seawater as electrolyte, and solar energy as an inexpensive electric source for co-electrolysis initiation makes the microreactor a low-cost and sustainable alternative for CO2 sequestration and synthesis of organic compounds.